(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Youth are projected as the most vociferous and vocalsection of the society and are active, energetic and vivacious. When theirenergy is channelized constructively it yields to a delightful future not onlyfor the youth but also for the whole nation.